1978
DOI: 10.1139/e78-157
|View full text |Cite
|
Sign up to set email alerts
|

Time evolution of stress under an artificial lake and its implication for induced seismicity

Abstract: The time history of stress beneath a realistic artificial Lake with a realistic loading history on a permeable lithosphere can be calculated by solving the consolidation equations for a uniform permeable medium. The evolution of stress conditions towards or away from a Mohr-Coulomb failure envelope illustrates that highest risk of induced seismicity exists at initial loading and in some cases after a down-draw of the lake. The calculated histories depend crucially on hydrologic and geologic conditions which ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Because larger magnitude induced earthquakes are generated on critically stressed, preexisting fault structures [ Simpson , ], it is important to understand the fault structures in areas that might be susceptible to induced earthquakes, preferably before human activities enhance the possibility of large earthquakes. Although computational observations show that reservoir‐induced earthquakes occur in varying tectonic environments and water levels [ Roeloffs , ], larger reservoir‐induced earthquakes may generally favor strike‐slip and normal faulting tectonic regimes [ Simpson , ; Bell and Nur , ; Withers and Nyland , ; Snow , ]; both types of faulting occur in fault releasing bends and fault step‐overs. Fault bends and step‐overs are common along strike‐slip fault systems, and these locations can be stress points for earthquake rupture nucleation or termination [ Aki , , ; Allen et al , ; Kruepfer , ].…”
Section: Discussionmentioning
confidence: 99%
“…Because larger magnitude induced earthquakes are generated on critically stressed, preexisting fault structures [ Simpson , ], it is important to understand the fault structures in areas that might be susceptible to induced earthquakes, preferably before human activities enhance the possibility of large earthquakes. Although computational observations show that reservoir‐induced earthquakes occur in varying tectonic environments and water levels [ Roeloffs , ], larger reservoir‐induced earthquakes may generally favor strike‐slip and normal faulting tectonic regimes [ Simpson , ; Bell and Nur , ; Withers and Nyland , ; Snow , ]; both types of faulting occur in fault releasing bends and fault step‐overs. Fault bends and step‐overs are common along strike‐slip fault systems, and these locations can be stress points for earthquake rupture nucleation or termination [ Aki , , ; Allen et al , ; Kruepfer , ].…”
Section: Discussionmentioning
confidence: 99%
“…It is intuitively clear that the weight of the full reservoir on the hanging wall of a thrust fault or on the foot wall of a normal fault tends to stabilize such faults. Several previous model studies based on simplified formulations [Bell and Nur, 1978;Withers and Nyland, 1978] have concluded that normal and strike slip faults directly beneath the reservoir are the most greatly destabilized faults and that destabilization of thrust faults at an edge of the reservoir is possible. The results presented here confirm these con- 5O • 4o o• 3o ,• 2o >• o '"'"""lf""""l"l"'"'"'"l'n"'""l"'"'"'"l"'"'"'"l ""'""" clusions and extend them by showing that the time during the annual water level cycle at which a fault is most destabilized also depends on the location and orientation of the fault, as well as on the diffusivity and Skempton's coefficient of the rock beneath the reservoir.…”
Section: Copyright 1988 By the American Geophysical Unionmentioning
confidence: 99%
“…The rate at which pore pressure responds at depth to the impoundment of the reservoir is a function of the permeability of the rock. Theoretical studies [Bell and Nur, 1978;Withers and Nyland, 1978] have considered the subsurface change in pore pressure due to reservoir impoundment. It is important to know the in situ permeability at Monticello Reservoir to compare the theoretical fluid diffusion time with the time history of seismicity so as to provide an additional test of our working hypothesis.…”
Section: Permeability Measurementsmentioning
confidence: 99%